Taylor Swift - Peppas, Lynn. (New York, N.Y. : Crabtree Pub., 2011)
Not many years ago, country music sensation Taylor Swift was singing karaoke and learning to play her first guitar. Today, the superstar singer and songwriter performs sold-out concerts around the world. Her albums sell millions of copies, she's won numerous music awards, and she's been on the cover of just about every popular magazine.
Who is Taylor Swift? -- Growing up Taylor Swift -- Swift rise to fame -- Taylor-made success.
Includes bibliographical references (p. 31) and index.
Keywords: Swift, Taylor, -- 1989- -- Juvenile literature; Women country musicians -- United States -- Biography -- Juvenile literature